2000
DOI: 10.1093/jnen/59.5.393
|View full text |Cite
|
Sign up to set email alerts
|

Lipoperoxidation Is Selectively Involved in Progressive Supranuclear Palsy

Abstract: Abstract. Progressive supranuclear palsy (PSP) is a neurodegenerative disorder characterized by extensive neurofibrillary tangle (NFT) formation and neuronal loss in selective neuronal populations. Currently, no clues to the biological events underlying the pathological process have emerged. In Alzheimer disease (AD), which shares with PSP the occurrence of NFTs, advanced glycation end products (AGEs) as well as oxidation adducts have been found to be increased in association with neurofibrillary pathology. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 20 publications
4
39
0
1
Order By: Relevance
“…The concentration of MDA we observed in post mortem brain of normal subjects is similar to that in reports employing the improved TBARS assay coupled to HPLC separation (Hayn et al, 1996;Lyras et al, 1997;Odetti et al, 2000) and in studies using the colorimetric assay based on reactions of the aldehyde to N-methyl-2-phenyl-indole (Yoshida et al, 2000;Schuessel et al, 2004). The brain levels of HNE we obtained (ϳ1 pmol/mg wet tissue) are within the physiological concentration range of HNE in biological tissues or fluids (ϳ1 M; Esterbauer et al, 1991) and also agree with those reported using direct HPLC/UV detection of HNE (Odetti et al, 2000).…”
Section: Discussionsupporting
confidence: 86%
“…The concentration of MDA we observed in post mortem brain of normal subjects is similar to that in reports employing the improved TBARS assay coupled to HPLC separation (Hayn et al, 1996;Lyras et al, 1997;Odetti et al, 2000) and in studies using the colorimetric assay based on reactions of the aldehyde to N-methyl-2-phenyl-indole (Yoshida et al, 2000;Schuessel et al, 2004). The brain levels of HNE we obtained (ϳ1 pmol/mg wet tissue) are within the physiological concentration range of HNE in biological tissues or fluids (ϳ1 M; Esterbauer et al, 1991) and also agree with those reported using direct HPLC/UV detection of HNE (Odetti et al, 2000).…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, tauopathy induces OS [40] . Some OS markers are notably increased in tauopathy, such as malondialdehyde and 4-hydroxynonenal [41][42][43] . The activation of antioxidant defenses is also observed in tauopathy [44,45] .…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of nitrotyrosine, a permanent marker of ONOO − attack on proteins, were previously demonstrated in Alzheimer's disease (AD), PD, and amyotrophic lateral sclerosis (ALS) (8). Increased levels of 4-HNE, the most cytotoxic product of lipid peroxidation (10), have also been documented in AD, PD, ALS, and other neurodegenerative diseases (112,113). Aging is a critical factor for GSH homeostasis.…”
Section: Neurodegenerative Diseases and Oxidative Stressmentioning
confidence: 99%